Pengaruh Harga, Kualitas Produk dan Lokasi terhadap Tingkat Penjualan dengan Keputusan Pembelian sebagai Variabel Intervening pada PT. Bintang Banjar Cemerlang - Irfan Perdana Dinata; Yulasmi Yulasmi; Yeki Candra (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of price, product quality, and location on sales levels, with purchasing decisions as intervening variables at PT. Bintang Banjar Cemerlang. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are consumers of PT. Bintang Banjar Cemerlang. The results of the study found that there was a significant effect between Price and Purchasing Decisions. There was a significant effect between Product Quality and Purchasing Decisions. There was no significant effect between Location and Purchasing Decisions. There was a significant effect between Price and Sales Level. There was no significant effect between Product Quality and Sales Level. There was no significant effect between Location and Sales Level. There was a significant effect between Purchasing Decisions and Sales Level. Purchasing Decisions were able to mediate Price and Sales Level.